First Insights into Whole Genome Sequencing of the Mycobacterium tuberculosis Complex: Molecular Diversity and Drug Susceptibility Patterns in Senegal - Abdou Padane; Seyni Ndiaye; Malle Gueye; Mamadou Nda; Marièma Sarr; Aminata Mboup; Marilyne Aza-Gnandji; Darrel Ornelle Elion Assiana; Ndèye Astou Dabo; Yacine Amet Dia; Mame Sokhna Gueye; Ndeye Ndack Cissé; et al. (Recent Trends in Infectious Diseases, 2025)
Background: We conducted a bibliographic analysis of the Mycobacterium tuberculosis complex (MTBC) in sub-Saharan Africa, which included the analysis of 8,139 genomic sequences from 34 of the 49 sub-Saharan African countries. Notably, only one complete sequence from Senegal was identified, which had been generated in the United States. Our primary objective was to utilize whole genome sequencing (WGS) to detect resistance in anti-tuberculous strains of the MTBC in Senegal. This work seeks to advance the understanding of the molecular diversity and distribution of tuberculosis in Senegal. Methods: A prospective study was conducted in Senegal involving patients diagnosed with tuberculosis (TB). Genomic DNA was extracted from positive culture isolates and subjected to whole genome sequencing (WGS) using Illumina MiSeq technology. This approach enabled the characterization of Mycobacterium tuberculosis complex (MTBC) species and lineages, as well as the identification of mutations associated with treatment resistance. The findings confirmed the significant presence of MTBC and diverse lineages in Senegal. Results: Our results showed that all strains isolated from patients were Mycobacterium tuberculosis sensu stricto, with a predominance of Euro-American sub-lineages. Through bioinformatics analysis, we predicted resistance to 20 anti-tuberculosis (first and second line) drugs for each sample. In silico antibiogram analysis identified strains resistant to isoniazid and other multi- drug-resistant strains, with resistance associated mutations detected in the katG and rpoB genes. Conclusion: This study significantly contributed to the molecular surveillance of Mycobacterium tuberculosis complex in Senegal. The species identification of M. tuberculosis isolates is crucial for the rapid diagnosis of tuberculosis in patients, thereby facilitating improved clinical management and treatment outcomes.
Keywords: Drug susceptibility test; Lineage 4; Molecular distribution; Mycobacterium tuberculosis complex; Senegal